2013
DOI: 10.1136/bmjspcare-2012-000327
|View full text |Cite
|
Sign up to set email alerts
|

The impact of advance care planning of place of death, a hospice retrospective cohort study

Abstract: ObjectivesThere is limited evidence of the impact of advance care planning (ACP) on outcomes. We conducted a retrospective cohort study on deaths of all patients known to a hospice in a 2.5-year period to see if use of ACP affected actual place of death, hospital use and cost of hospital care in the last year.Results969 patients were included. 550 (57%) people completed ACP. 414 (75%) achieved their choice of place of death. For those who chose home, 34 (11.3%) died in hospital; a care home 2 (1.7%) died in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 9 publications
1
76
0
Order By: Relevance
“…All but four of the 18 included studies are from the US, with two from the UK (Abel et al, 2013;Baker et al, 2012), one from Canada and one from Singapore .…”
Section: Countrymentioning
confidence: 99%
“…All but four of the 18 included studies are from the US, with two from the UK (Abel et al, 2013;Baker et al, 2012), one from Canada and one from Singapore .…”
Section: Countrymentioning
confidence: 99%
“…4,137 Some studies have reported benefits. 128,[130][131][132]138,139 These tend to be based on surveys, and to focus on a comparative reduction in days and deaths in hospital and costs associated with care in the last year of life. Detering et al 128 report the results of a randomised controlled trial in Australia in which patients receiving a structured ACP intervention were more likely to die in their preferred place.…”
Section: 114mentioning
confidence: 99%
“…Carers expressed increased satisfaction with EOLC, and costs for health care were reduced. Abel et al 132 conducted a retrospective cohort study of deaths among known hospice users and concluded that those who had an ACP in place spent fewer days in hospital and had lower costs of care than those without. However, a growing body of qualitative evidence gives an indication of the great complexity, ambivalence and variability of patients' desire to engage in ACP, and their responses to professional invitations to do so.…”
Section: 114mentioning
confidence: 99%
See 1 more Smart Citation
“…65 In one study, such an approach reduced both days and costs of hospitalisation in the last year of life by almost one-third. 66 Inappropriate overinvestigation and over-treatment of older patients with multimorbidity can be minimised by management approaches that integrate care-specific benefit-harm trade-offs with life expectancy, care goals and patients' values and preferences. 67 …”
Section: Adopt a More Conservative Approach Nearing The End Of Lifementioning
confidence: 99%